THE MISERY OF AN ALCOHOLIC’S LIFE PORTRAYED IN PAULA HAWKINS’ THE GIRL ON THE TRAIN - Aditya, Aldi; Saprudin, Saprudin; Sukmawaty, Fenty (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
This research is entitled "The misery of an alcoholic's life portrayed in Paula Hawkins' the Girl on the Train.". The purpose of this study is to describe the background of the misery experienced by Rachel's character. A poor woman who has an unlucky fate and her life is full of sadness. The approach used in this research is a psychoanalytic approach. The method used in this research is descriptive qualitative. The results of this study indicate that one of the causes of Rachel's misery is the effect of alcohol. Rachel is an alcoholic, so it's hard to control herself. Throughout the story in this novel, alcohol is one of the most dominating and has an impact on Rachel. Rachel has an internal conflict. She experienced conflict with herself, on the one hand she tried to stop being an alcoholic but her intentions always failed because she was an alcoholic who was classified as acute. Some serious problems appear from this alcohol addiction. From the results of the analysis, it was found that alcohol was behind Rachel's misery, including divorce, job loss and depression. Keywords: Misery, Paula Hawkins, The Effect of Alcohol, Alcoholic, internal conflict, psychoanalytic approach